Molecular understanding of charge storage and charging dynamics in supercapacitors with MOF electrodes and ionic liquid electrolytes - Bi, Sheng; Banda, Harish; Chen, Ming; Niu, Liang; Chen, Mingyu; Wu, Taizheng; Wang, Jiasheng; Wang, Runxi; Feng, Jiamao; Chen, Tianyang; Dincă, Mircea; Kornyshev, Alexei A.; et al. (Nature materials, 2020)
We performed constant-potential molecular dynamics simulations to analyse the double-layer structure and capacitive performance of supercapacitors composed of conductive metal–organic framework (MOF) electrodes and ionic liquids. The molecular modelling clarifies how ions transport and reside inside polarized porous MOFs, and then predicts the corresponding potential-dependent capacitance in characteristic shapes. The transmission line model was adopted to characterize the charging dynamics, which further allowed evaluation of the capacitive performance of this class of supercapacitors at the macroscale from the simulation-obtained data at the nanoscale. These ‘computational microscopy’ results were supported by macroscopic electrochemical measurements. Such a combined nanoscale-to-macroscale investigation demonstrates the potential of MOF supercapacitors for achieving unprecedentedly high volumetric energy and power densities. It gives molecular insights into preferred structures of MOFs for accomplishing consistent performance with optimal energy–power balance, providing a blueprint for future characterization and design of these new supercapacitor systems. The electrochemical performance of supercapacitors can be enhanced with porous electrodes. Molecular dynamics simulations can now help to clarify the double-layer structure and capacitive performance of supercapacitors composed of MOF electrodes and ionic liquid electrolytes.